2021
DOI: 10.3390/vaccines10010060
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of COVID-19 Vaccine Confidence: Findings from Slums of Four Major Metro Cities of India

Abstract: There are limited studies on COVID vaccine confidence at the household level in urban slums, which are at high risk of COVID-19 transmission due to overcrowding and poor living conditions. The objective was to understand the reasons influencing COVID-19 vaccine confidence, in terms of barriers and enablers faced by communities in urban slums and informal settlements in four major metro cities in India. A mixed method approach was adopted, where in field studies were conducted during April–May 2021. First, a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…It, consequently, resulted in long wait times in queues. Consistent with our finding, the uncertainty of not getting vaccinated and the nature of the registration process have been reported among women and older people as barriers against COVID-19 vaccination [54].…”
Section: Barriers To Covid-19 Vaccines Uptakesupporting
confidence: 92%
See 1 more Smart Citation
“…It, consequently, resulted in long wait times in queues. Consistent with our finding, the uncertainty of not getting vaccinated and the nature of the registration process have been reported among women and older people as barriers against COVID-19 vaccination [54].…”
Section: Barriers To Covid-19 Vaccines Uptakesupporting
confidence: 92%
“…From the narratives, there were misconceptions that COVID-19 vaccines were demonic/satanic, could cause infertility in both men and women and it is meant to kill Africans, including Ghanaians. Tamysetty et al’s [ 54 ] study in India reported similar misconceptions, including the belief that the COVID-19 vaccine could increase the risk of death and decrease a woman’s ability to conceive children. Studies have also documented that some Christians associate the COVID-19 vaccine with the mark of the beast/666 [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 97%
“…A similar finding was observed among migrants, another vulnerable population in Shanghai, China, where three in fourth respondents showed higher confidence levels in vaccine safety and effectiveness (48). In contrast, some constraints might be responsible for lessening the vaccine uptake, such as family dynamics and gender, geographical and technological barriers, and socioeconomic reasons (49). The respondents had a high level of calculation of information regarding the effectiveness and more details about the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 pandemic showed challenges and barriers to vaccinating communities even in urban areas. Role of community-based organizations and groups is invaluable in conveying appropriate messages to the general public 31 .…”
Section: Community Participation Communication and Behavioural Changementioning
confidence: 99%